Co-evolution between etailing and parcel express industry and its geographical imprints: The case of China. (June 2015) - Wang, James J.; Xiao, Zuopeng
Highlights: This study conceptualizes the relationship between etailing (e-retailing) and the parcel express industry (PEI) and analyzes their co-evolution in China. Four operational models of etailing are discussed in the context of their intertwining relations with different forms of parcel express services. Two major geographical imprints are explained and conceptualized. Different strategies demonstrate that co-evolution is not only a path-dependent process but associated with place-dependent institutions. A geographical impact of the co-evolution is the co-location of supply-chain-based etailers with high demand density, favoring large cities. Abstract: This study conceptualizes the relationship between etailing (e-retailing) and the parcel express industry (PEI) and analyzes their co-evolution in China. Four operational models of etailing are discussed in the context of their intertwining relations with different forms of parcel express services. This co-evolution generated compound outcomes because of the late start of PEI and the fast growth of online shopping in China. These four models coexist, with two standing out as major types that suggest future directions. Two major geographical imprints of this process are explained and conceptualized: (1) the zonal delivery strategy by supply-chain-based e-merchants, which is conceptualized into a choice model of order-fulfilling locations to strengthen timely delivery; and (2) the Baoyou strategy advocated by e-market-based retailers and their logistic support for a slower, low-cost market of larger geographical coverage compared to the first strategy. Both strategies demonstrate that co-evolution is not only a path-dependent process but is also associated with place-dependent institutions.